2017
DOI: 10.1016/s2542-5196(17)30162-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surgery on global climate: a carbon footprinting study of operating theatres in three health systems

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
380
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 492 publications
(413 citation statements)
references
References 19 publications
7
380
0
26
Order By: Relevance
“…The health care sector could also reduce carbon emissions that occur in the global production chain of medical goods and pharmaceuticals by applying green procurement strategies. Expenditures could be reallocated to less carbon intensive forms of health care provision by changing medical procedures [34][35][36][37], or by using functionally equivalent drugs and medical devices with lower carbon intensity of production and packaging [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…The health care sector could also reduce carbon emissions that occur in the global production chain of medical goods and pharmaceuticals by applying green procurement strategies. Expenditures could be reallocated to less carbon intensive forms of health care provision by changing medical procedures [34][35][36][37], or by using functionally equivalent drugs and medical devices with lower carbon intensity of production and packaging [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…This includes pharmaceuticals and equipment, both of which are central to the practice of anaesthesia and contribute to making operating theatres one of the most resource‐intensive locations in healthcare. Annually, each operating theatre generates 2.3 tonnes of solid waste and the equivalent of 188 tonnes of CO 2 . Anaesthetists are intimately involved with resource use; the ‘hands‐on’ nature of the specialty means that unlike many of our medically‐qualified colleagues we administer medications and handle disposables and equipment personally.…”
Section: The Effect Of Healthcare On the Environmentmentioning
confidence: 99%
“…Of the halogenated hydrocarbons, desflurane has the highest environmental impact due to its atmospheric persistence (14 years), with a 100‐year global warming potential (GWP 100 ) 2540 times that of an equal mass of CO 2 (sevoflurane 130, isoflurane 510 times) . Although there are strategies which can minimise the volume of inhalational agent used clinically, the potency of anaesthetic vapours as greenhouse gases is such that techniques which avoid their use altogether, including regional anaesthesia and total intravenous anaesthesia (TIVA) are likely to be preferable from an environmental perspective.…”
Section: Changing Practicementioning
confidence: 99%
“…A comparison of the UK, Canada and the USA found that emissions per case varied between 140 and 240 kg per case, and the true spread may have been even wider as the carbon costs of procurement and hospital waste were not fully captured in the calculations. 30 Interventions to reduce the costs of surgery include better processes for managing waste from operating theatres, 31 scavenging or minimizing the use of anaesthetic gases that are significant climate-polluters (desflurane and N 2 O in particular) and switching health care facilities to renewable sources of electricity. 25 There is much to learn from the experience of countries like the UK that have been early adopters of lower carbon health care.…”
Section: What This Means For Health Care and In Particular For Surgeonsmentioning
confidence: 99%